Question: analytical solution

January 13 2014 goli 130
Maple

0

Dear guys. I want to solve this equation analytically:

diff(Q(t),t)^2 = ln(t)^(b) + b*ln(t)^(b-1)

I think it is impossible. So I assumed that diff(Q(t),t)^2 = diff(P(t),t) and now I can solve it for P(t) easily. I obtained:

P(t) = t*ln(t)^(b)

Now, I want to know that there is anyway to obtain Q(t) using the latter relation and  diff(Q(t),t)^2 = diff(P(t),t) ?

Also I have a function as V(P)=P^(-2). What can I say about the behaviour of V(Q)?

Thanks a lot.

Please Wait...